FOOD SECURITY IN THE MUNICIPALITY OF JOSÉ DE FREITAS - PI: CHALLENGES AND LOCAL POLICIES TO COMBAT FOOD INSECURITY - Paulo Moreira dos Santos, João; Carlos Rodrigues da Mata, Luis; Henrique Ferreira da Silva, Francisco (Revista Gênero e Interdisciplinaridade, 2026)
Food and Nutritional Security (FNS) is crucial for human development and for reducing social vulnerabilities. In medium-sized municipalities such as José de Freitas–PI, local food production, access to food, and governance make this issue particularly relevant. This article indicates that FNS in the municipality faces several challenges, contemporary public policies, and issues related to the role of family farming. The study is qualitative and exploratory, conducted through documentary surveys, an updated literature review (2020–2025), semi-structured interviews with the Municipal Secretary of Agriculture, and direct observations of the local context, with a focus on the “Mãos que Alimentam” Program. The results show that the municipality implements structural policies that enhance food production and distribution, especially through the “Mãos que Alimentam” Program, which connects family farmers to distribution logistics and technical support. However, structural and institutional limitations — such as logistical constraints, low representation in the Municipal Food Security Council, and the absence of quantitative data on food consumption — reduce the effectiveness of the implemented actions. The study also highlights an increase in the consumption of ultra-processed foods, revealing weaknesses in local dietary habits. The progress achieved by José de Freitas in promoting FNS and strengthening family farming is discussed, yet it remains necessary to reinforce governance, infrastructure, and policy oversight to ensure a more just, equitable, sustainable, and integrated food system.